G88(P) The FINISH Course: A novel acute care consultant role simulation course. (27th April 2016) - Lee, L; Davies, P; Batra, D; Schoonaker, B; Smith, S; Smith, C
Abstract : Aims: Complex multitasking, multiple pressures, and frequent demands on a new consultant are daunting. We designed a course to give candidates extension beyond their clinical knowledge. We describe the inspiration, delivery, and feedback from our novel all day Consultant role simulation course aimed at ST8 paediatric trainees Methods: A full day simulation course devised for final year paediatric trainees, to support transition to Consultant working. Simulation components included: Leading a neonatal resuscitation Dealing with complex ward situations Preparing a written media statement A media interview Emergency department resuscitation Speaking to parents about a complaint Office time with inbox problems Speaking to the Coroner and tertiary experts Analysing a service improvement problem A handover to the evening consultant Delivering a short presentation The simulation events were run continuously and in parallel, demanding real time prioritisation, time management, leadership and managerial skills. Candidates were also expected to demonstrate their ability to prioritise their 'inbox' tasks and prepare a presentation. The day was delivered by senior trainers, simulation experts and professional actors in a bespoke simulation centre. Results and feedback: Feedback was very positive after a long, intensive day. On a 1–5 scale candidate scores were: Highest rated session was the media session scoring 4.8. Mean score for all sessions was 4.5, with no session scoring below 4.2. Conclusion: Our feedback shows there is a need and desire for a course which exposes trainees to some of the aspects of being a consultant which are not otherwise addressed. The use of professional actors improved the fidelity of the course and the reliability of the simulations. We believe this course is an important addition to training.